Penguatan Nalar Kritis dan Etis Melalui Metode Dialog Sokratis Berbasis Epistemologi Filsafat Islam di Madrasah Aliyah, Kab. Agam - Muallim Lubis; Asrul Harahap; Andri Umar Saleh Lubis; Iqbal Rizkyka (AL-IMAM: Journal on Islamic Studies, Civilization and Learning Societies, 2026)
Strengthening critical and ethical reasoning has become a strategic necessity in Madrasah Aliyah education amid increasing social complexity and information disruption. Learning practices at MAN 2 Agam, MAS MTI Ghobah, and MAS Mu’allimin Sawah Dangka remain predominantly characterized by normative and factual approaches, thereby limiting opportunities for reflective dialogue. This article examines the effectiveness of a reflective, dialogical, and participatory Islamic philosophy approach in enhancing students' reasoning abilities. The study employs Participatory Action Research (PAR), encompassing the stages of problem identification, strategy design, implementation of dialogical problem-posing classrooms, and continuous reflection. The intervention was carried out through Islamic philosophy workshops, Socratic dialogue, and the integration of exploratory and evaluative questioning. Students' participation in classroom discussions demonstrated more active and purposeful engagement, accompanied by an improved ability to construct rational arguments in a more systematic manner. The dialogical process was characterized not only by the exchange of ideas but also by the emergence of ethical considerations in every response expressed by the participants. Meanwhile, teachers' instructional practices underwent a noticeable transformation, particularly in their questioning techniques, which shifted from one-way transmission toward analytical and reflective exploration. These findings indicate that the Islamic philosophy approach is capable of fostering a meaningful and functional integration of rationality and morality within madrasah learning.